2021
DOI: 10.35508/jhbs.v3i4.4196
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Knowledge, Attitudes and Social Status of Family Heads Against Dengue Prevention Measures in the Oesapa Health Center Work Area in 2020

Abstract: DHF is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The factors that cause a person to suffer from dengue are environmental factors, knowledge, attitudes, and social status. This study aims to analyze the relationship between knowledge, attitudes, and social status of the head of the family on the prevention of DHF. The type of research used is quantitative research with a cross-sectional approach. The number of samples in this study was 100 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results of this study are in line with previous research conducted by Harapan et al (2018), with the results of the study showing that there is a significant relationship between knowledge and attitudes toward preventing dengue disease and people who had good knowledge were 2.7 times more likely to have good attitudes, and people who had good attitudes were 2.2 times more likely to have good practices regarding dengue (13). Previous research conducted by Mbani et al (2021) showed that there is a relationship between the knowledge and attitudes of the head of the family and the prevention measures of DHF in the Oesapa Health Center working area in 2020 (14). The results of the study using Chi-Square get a p-value <0.0001.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are in line with previous research conducted by Harapan et al (2018), with the results of the study showing that there is a significant relationship between knowledge and attitudes toward preventing dengue disease and people who had good knowledge were 2.7 times more likely to have good attitudes, and people who had good attitudes were 2.2 times more likely to have good practices regarding dengue (13). Previous research conducted by Mbani et al (2021) showed that there is a relationship between the knowledge and attitudes of the head of the family and the prevention measures of DHF in the Oesapa Health Center working area in 2020 (14). The results of the study using Chi-Square get a p-value <0.0001.…”
Section: Discussionsupporting
confidence: 90%
“…Digital technology is beneficial during the Covid-19 pandemic for conducting dengue surveillance. The existence of a social restriction policy with social distancing has caused the door-to-door control program not to be implemented [11], [12], [13].…”
Section: Responsementioning
confidence: 99%
“…There are several studies in Indonesia regarding attitudes toward dengue control. A study in Kupang, Indonesia, explains that a significant relationship exists between knowledge, attitudes, and actions in controlling dengue 11 . Likewise, other studies in Indonesia show that knowledge and attitudes influence dengue prevention measures 12,13 .…”
Section: Open Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is consistent with previous studies, which show that unemployed individuals are more likely to contract DHF (Damayanti, & Mega, 2022). In contrast, a study conducted in East Nusa Tenggara, observing all respondents who contracted DHF, found that they were employed (Mbani, Limbu, & Landi, 2021).…”
Section: Discussionmentioning
confidence: 88%